(untitled) (Research, Society and Development, 2020)
The objective of this study was to analyze the precariousness of work in the mobile emergency care service in the view of health workers and discuss the implications for the health of professionals. Qualitative, descriptive and exploratory research conducted with 18 workers (nurses, doctors and nursing technicians) of a mobile emergency care service in the city of Rio de Janeiro, in 2017. In data collection, we worked with the technique interview by means of a script and the registration of sociodemographic and occupational data a structured instrument. Applied to thematic content analysis to the testimonials. In the participants’ view precarious work causes psychological distress due to the absence of labor rights provided for by law, the fear of unemployment and the absence of social protection. It is concluded that professionals who work only in the mobile emergency care service are more vulnerable to psychological distress in the face of fear of unemployment and lack of social protection. It is concluded that there is a need for workers’ health support by the organization in view of the exposure of staff to occupational risks and job insecurity.